River or lake in South Fork Kuskokwim River Valley, Alaska, August or September 1914 - University of Washington Libraries. Special Collections Division.
McPherson number: K366 PH Coll 495.2-22d Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.